Matrix‐assisted ionization Fourier transform mass spectrometry for the analysis of lipids. (31st January 2019) - Liyanage, Rohana; Gidden, Jennifer; Wilkins, Charles L.; Lay, Jackson O.
Abstract : Rationale: Assessing the utility of vacuum matrix‐assisted ionization (MAI) for the direct and rapid analysis of lipids in complex samples with emphasis on bacterial taxonomy. Methods: Matrix‐assisted ionization Fourier transform mass spectrometry (MAI‐FTMS) was used to characterize polar and non‐polar lipids in mixtures. Results: For non‐polar lipid triacylglycerols (TAGs), MAI‐FTMS produced lipid‐specific ions for eight different edible oils and allowed these oils to be identified based on their MAI‐FTMS profiles. For polar lipids from bacteria, MAI‐FTMS of crude lipid extracts allowed taxonomic identification of eight blind‐coded samples based on taxonomy‐specific phospholipid profiles. MAI produced results comparable and complementary to benchmark MALDI and ESI methods currently used for characterization of polar and non‐polar lipids in the same mixtures. Conclusions: The newly developed MAI technique is a rapid, simple and complementary method for the characterization of polar and non‐polar lipids in complex mixtures.